TREN PARIWISATA DKI JAKARTA - Nugraha, Rizki Nurul; Yuliantini, Tine; Karyatun, Subur (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
This research will explain tourism trends in Jakarta and various information related to obstacles that occur in the field. As a leading tourist area, DKI Jakarta can provide more complete information about tourist characteristics. A qualitative approach is used by taking respondents as many as 100 archipelago tourists and 10 Tourism Services Industry using accidental sampling, with one shot time method, where time is used only one time. The results of the study identified constraints in marketing in Jakarta, including airline ticket prices, relatively high tour package prices, low demand, and media competition. The implications and suggestions are explained in the article. Keywords: Jakarta tourism, market characteristics